Integration of universities in the context of reforms of higher education: European experience and Russian practice - M. A. Korytsev; A. V. Ipatova; I. O. Nikolaenko (Russian Journal of Economics and Law)
Objective: to identify the institutional features of the processes of universities integration within the modern reforms of higher education in Russia and European countries.Methods: comparative institutional analysis of the main parameters of the reforms aimed at universities integration. Results: the institutional specificity of reforms aimed at the universities integration is revealed. Through specific illustrations and characteristics of the ongoing reforms in a number of European countries (Great Britain, Romania, Spain) and the United States, the relationship is demonstrated between the institutional environment of the national higher education systems, the characteristics of the socio-economic and demographic situation in these countries, and the results of the reforms. A possible range of forms and types of integration and interaction of universities, including their merger (acquisition), as well as various forms of long-term cooperation (alliances), is shown; some advantages of these forms are described. Scientific novelty: based on the comparative institutional analysis and the study of international experience in universities integration, the author reveals the institutional specifics of reforms in some countries and specifies the possibilities of using both mergers (acquisitions) of universities and some types of long-term associative interaction between individual universities in order to improve the quality of the provided services, research, and internationalization of education process. Practical significance: the obtained results can be used to specify the public policy in the sphere of higher education and science in order to adjust the forms of effective interaction of universities to improve the quality of educational services and research.